INTERPRETASI HERMENEUTIK PUISI PEMBIDAS KARYA AJAMUDDIN TIFANI - Agus Yulianto (TELAGA BAHASA, 2017)
This “Pembidas “of Ajamuddin Tifani is a poetry that has lots of positivemeanings. The purpose of this study was to understand the integral meaning of poetry Pembidas by Ajamudddin Tifani by using a hermeneutic approach. The problem of this study describes the meaning of Pembidas by using hermeneutic approach. This study used descriptive qualitative method with data analysis technique in each line of poetry and then proceeded as a whole. Based on the result of the analysis, it can be seen that the meaning of Pembidas is about the disobedient of human against his/ her God. This has actually taken place for a long time since the days of the Madyan, Rass, Thamud, and Sodom. They are the people who make idols and passions as their Lord. However, in modern times like this, their disobedient is slightly transformed. They continue to worship idols, but not as sculptures but in the form of money, possessions, and technology.